208k views
1 vote
Solve 4^x-5 = 6 for x using the change of base formula log base b of y equals log y over log b

2 Answers

5 votes

Answer:

6.292

Explanation:

I got it right on the test.

User Rick Westera
by
5.3k points
4 votes

Answer:


4^x-5=6 gives the solution
x=(\log(11))/(\log(4)).


4^(x-5)=6 gives the solution
x=(\log(6))/(\log(4))+5.

Explanation:

I will solve both interpretations.

If we assume the equation is
4^(x)-5=6, then the following is the process:


4^x-5=6

Add 5 on both sides:


4^x=6+5

Simplify:


4^x=11

Now write an equivalent logarithm form:


\log_4(11)=x


x=\log_4(11)

Now using the change of base:


x=(\log(11))/(\log(4)).

If we assume the equation is
4^(x-5)=6, then we use the following process:


4^(x-5)=6

Write an equivalent logarithm form:


\log_4(6)=x-5


x-5=\log_4(6)

Add 5 on both sides:


x=\log_4(6)+5

Use change of base formula:


x=(\log(6))/(\log(4))+5

User Ryan Morton
by
5.6k points